Outcomes of V-Y Anoplasty Technique in The Management of Moderate to Sever Post Hemorrhoidectomy Anal Stenosis - Zakaria, Reham; Metwalli, Abd-Elrahman M.; Hegab, Yasmine Hany; Orban, Yasser A. (Journal of Coloproctology, 2025)
Anal stenosis is a very annoying complication after anorectal surgery. Moderate and severe cases often need surgery.The aim of the study is to evaluate the efficacy and outcomes of an anoplasty technique (V-Y advancement flap) for management of moderate to severe post- hemorrhoidectomy anal stenosis.This is a randomized clinical study that was performed on 25 patients with post- hemorrhoidectomy anal stenosis and treated with anoplasty (V-Y advancement flaps) technique in the department of general surgery in a well specialized center from December 2023 to December 2024. Patients were monitored for Pain levels scoring and postoperative complications were analyzed.The mean age of the study contributors was 36.4 ± 5.25. The gender distribution showed a higher number of males (16) as compared to females (9). 5 patients had severe anal stenosis, while 20 patients had moderate anal stenosis. Mean preoperative VAS score was 6.2 ± 1.4. Follow up at 1, 3 and 6 months showed decrease in VAS score with significant improvement of symptoms. As regards post-operative complications, there was only one patient (4.0%) who presented with postoperative mild bleeding, also one patient (4.0%) suffered from urine retention, two patients (8.0%) had wound dehiscence, one patient (4.0%) patient presented by transient gas incontinence and one patient (4.0%) presented by mild restenosis.V-Y flap anoplasty is a safe, simple and effective procedure for management of moderate and severe post-hemorrhoidectomy anal stenosis with marked improvement of patient symptoms and low complication rates.
Keywords: anal stenosis; anoplasty; V-Y advancement flap